PROPOSAL FOR SERBIAN TOURISM DESTINATIONS MARKETING CAMPAIGN - Paunović, Ivan (The European Journal of Applied Economics, 2013)
Serbia is geographically located in Europe, which is why it faces stiff competition from other European destinations, but also from other destinations worldwide. In order to understand contemporary competitive environment, major trends have been identified at the global, regional and local level. The data from the analysis of Serbian summer season tourism market were used to create tourist profiles for 4 supply side regions (Domestic-Serbia; Western Balkans-Slovenia, Croatia, Bosnia, Montenegro, Kosovo and Macedonia; Central-Eastern Europe-Austria, Czech Republic, Slovakia, Poland, Hungary, Romania; Western Europe and the rest of the world), for 5 major Serbian destinations (Belgrade, Novi Sad, Niš, Zlatibor, Kopaonik) and for 7 types of tourists according to their core motivation for travelling (pleasure, fun & entertainment, nature, culture, sport & adventure, health, and business). Based on the given tourist profiles, separate marketing campaign scenarios were created for each of the market segments.
Keywords: tourism marketing campaign; tourist profiles; destination marketing; market research; market segmentation